Targeted Expression to Liver of an antimiR-33 Sponge as a Gene Therapy Strategy against Hypercholesterolemia: In Vitro Study - Mariela Montaño-Samaniego; Jorge Sánchez-Cedillo; Amellalli Lucas-González; Diana M. Bravo-Estupiñan; Ernesto Alarcón-Hernández; Sandra Rivera-Gutiérrez; José Abraham Balderas-López; Miguel Ibáñez-Hernández (Current Issues in Molecular Biology, 2023)
Atherosclerosis is the leading cause of cardiovascular diseases in Mexico and worldwide. The membrane transporters ABCA1 and ABCG1 are involved in the reverse transport of cholesterol and stimulate the HDL synthesis in hepatocytes, therefore the deficiency of these transporters promotes the acceleration of atherosclerosis. MicroRNA-33 (miR-33) plays an important role in lipid metabolism and exerts a negative regulation on the transporters ABCA1 and ABCG1. It is known that by inhibiting the function of miR-33 with antisense RNA, HDL levels increase and atherogenic risk decreases. Therefore, in this work, a genetic construct, pPEPCK-antimiR-33-IRES2-EGFP, containing a specific antimiR-33 sponge with two binding sites for miR-33 governed under the PEPCK promoter was designed, constructed, and characterized, the identity of which was confirmed by enzymatic restriction, PCR, and sequencing. Hep G2 and Hek 293 FT cell lines, as well as a mouse hepatocyte primary cell culture were transfected with this plasmid construction showing expression specificity of the PEPCK promoter in hepatic cells. An analysis of the relative expression of miR-33 target messengers showed that the antimiR-33 sponge indirectly induces the expression of its target messengers (ABCA1 and ABCG1). This strategy could open new specific therapeutic options for hypercholesterolemia and atherosclerosis, by blocking the miR-33 specifically in hepatocytes.